¡Se Vende!: El Impuesto a la Renta en la Enajenación de Inmuebles Efectuada por Personas Naturales - Shulca Romero, Estefanía (2014)
This article discusses the treatment of the income tax of second category generated from the sale of real property made by individuals. Its development will focus on the following points:1) The tax determination described sequentially and according to law; 2) The exceptionalcases where there is not capital gain on the sale of a real property; 3) The determination ofthe tax basis in the cases where the transferor acquired free of charge the property that willbe transferred; 4) The obligation of using means of payment accepted by the banking andfinancial system in the operation; 5) The opportunity to pay the tax; 6) The exchange rate tobe used when the operation is performed in foreign currency; 7) The resolution of everydaylife cases related to the tax calculation; and 8) The summary of the main points of this article.